Increase in Synchronization of Autonomic Rhythms between Individuals When Listening to Music - Bernardi, Nicolò F.; Codrons, Erwan; di Leo, Rita; Vandoni, Matteo; Cavallaro, Filippo; Vita, Giuseppe; Bernardi, Luciano (Frontiers in Physiology, 2017)
In light of theories postulating a role for music in forming emotional and social bonds, here we investigated whether endogenous rhythms synchronise between multiple individuals when listening to music. Cardiovascular and respiratory recordings were taken from multiple individuals (musically trained or music-naïve) simultaneously, at rest and during a live concert comprising music excerpts with varying degrees of complexity of the acoustic envelope. Inter-individual synchronization of cardiorespiratory rhythms showed a subtle but reliable increase during passively listening to music compared to baseline. The low-level auditory features of the music were largely responsible for creating or disrupting such synchronism, explaining 80% of its variance, over and beyond subjective musical preferences and previous musical training. Listening to simple rhythms and melodies, which largely dominate the choice of music during rituals and mass events, brings individuals together in terms of their physiological rhythms, which could explain why music is widely used to favour social bonds.